Penerapan UML Sistem Informasi Penerimaan Mahasiswa Baru Pada Universitas Sepuluh Nopember Papua - Estevina Carolina Bagre; Putra Immanuel Pali; Melki Sendoni Wondiwoi; Nur Atya; Jered Imanuel Wanda; Tirsa Meira Pontoh; Marcella Putri Pentury; Herlina Lenora Yowei; Elia Mando Wanggai; Gladis Dominica Ngaderman; Helson Matuan; Sandra Keke Waromi; Imelda Numberi; Patmawati Hasan (CV Edujavare Publishing, 2025)
In the digital era, the use of information technology is the main need to improve administrative efficiency in various sectors, including higher education. Universitas Sepuluh Nopember (USN) Papua faces obstacles in the process of admitting new students which are still carried out manually, causing various problems such as inefficiency, risk of data errors, and limited information. To overcome this, this study aims to design a new student admission information system using the Unified Modeling Language (UML) approach that is able to describe the system visually, structured, and easy to understand. The research method used is software engineering with data collection techniques through observation and interviews. The results of the system design are visualized through use case diagrams, activity diagrams, sequence diagrams, and class diagrams to model the process and structure of the system as a whole. It is hoped that the results of this research can provide information system solutions that are more effective, efficient, and support transparency and accountability in the process of accepting new students in the university environment.